A imagem nômade : refotografar, reenquadrar e reapresentar imagens - Telles, Luísa Ribeiro (2019)
This research investigates the migration of images in the ages of mechanical and digital reproduction. How do images currently circulate? While the modernist avant-garde entailed an aesthetic and media transformation based on visuality, postmodernism intensified the gravitation towards interdisciplinarity. In the 21st century, our culture is dominated by pictures, visual simulations, illusions, copies, and reproductions to the extent that visual paradigms even threaten discursive practices. Under the aegis of the image, in this study the works from Aby Warburg to Gerhard Richter, and from Sherrie Levine to Camille Henrot were investigated. That is, found photos clipped from newspapers, magazines, or books; photos taken by the artists themselves; or, since the advent of the Internet, photographs and reproductions of photographs taken online and presented in strictly serial or in extremely unconventional combinations and arrangements. According to Groys, within this flow of images the value of a single photograph is being diminished and replaced by the notion of a stream of data in which both images and their significances are in a state of flux. This capacity of reproduction and circulation undermines the notion of an artwork’s singularity, as well as the status of the original and its imitation. If whether or not all things are equally reproducible was one of the central questions of modern art, as theorized by Benjamin. When the mechanical repetition becomes digital however, it no longer requires a pre-existing original which can be perceived as such. As postulated by Crimp, artworks are not defined anymore by their cult value, but instead are characterized by their exhibition value; in other words, by its ability to circulate. The postmodern age is characterized by a complex interplay of dislocations and relocations, of deterritorializations and reterritorializations, of de-auratizations and re-auratizations. Within this migration, the installation Eros Topography is finally here presented as contemporary to an era of thinking machines, algorithmic processing, and vast computational speeds